A new model for accurate estimation of gas content and pressure based on Langmuir adsorption equation in Guizhou, China - Qingsong Li; Enyuan Wang; Zhengpeng Duan; Junkui Zhu; Jiahao Wu (Adsorption Science & Technology)
In order to obtain the functional relationship of gas content and gas pressure, and to accurately calculate the two values which fitting the characteristics of coal seam, the destruction coefficient (X) and the index (ΔP) of the initial velocity of gas emission are introduced to establish the new model with higher precision based on Langmuir equation and destruction type of coal. The applicability of classic model (W-P model) and new optimization model in Guizhou mining areas are studied through the statistics of basic parameter data from 107 groups of coal-seam gas in eight mining areas. The results show that the gas content calculated by the classical model is lower than the measured value, while the gas pressure value is larger than that. The average relative error of gas content and pressure data reach 23.98% and 97.86%, respectively. The gas content and pressure data calculated by the optimization model are well fitted with the measured value. The fitting degree gradually rises with the increase of the sample size, and the average relative errors are 6.44% and 14.27%, respectively. Compared with the classical model, the average relative errors of gas content and pressure calculated by the optimization model reduce by 17.54% and 83.59%, respectively. The optimization model controls the tendency of calculated value error which significantly rises as the ΔP increases. For the coals with different destruction types, the average relative error of calculated gas content in optimization model ranges from 4.40% to 11.99%. And the average relative error of calculated pressure value ranges from 9.84% to 25.80%, both of them are far superior to that of classical model. The optimization model is more accurate for calculating the gas content and pressure in Guizhou.